2020
DOI: 10.57084/jmb.v1i1.232
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Brand Image Dan Word Of Mouth Communication Pada Keputusan Pembelian Produk Susu Dancow Di Bandar Lampung

Abstract: Marketing activities is one of the factors that affect the progress of the company. The term Brand image is a representation of the overall perception of the brand and is shaped from the past information and experience of the brand. The market has widely available various types of mass produced goods, consequently consumers are faced with many product choices, one of which is Dancow milk that competes with other brands of milk. he results show that the brand image and word of mouth together affect the decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Kotler and Keller (2016: 258) a brand image is a name, term, sign, symbol, design, or combination of these things that are used to identify products or services from one seller or group of sellers and to distinguish them from competitors. Previous research conducted by Husen et al, (2018), Apriliani (2019), Effendi et al, (2020), Dekasari & Hendri (2020), Miati (2020), andYoeliastuti et al, (2021), stated that brand image has a positive effect on purchasing decisions. Based on this description, the hypothesis can be explained as follows: H1: it is suspected that brand image has a positive effect on product purchasing decisions at Hotmie Padurenan.…”
Section: Literature Review the Effect Of Brand Image On Purchasing De...mentioning
confidence: 94%
See 2 more Smart Citations
“…According to Kotler and Keller (2016: 258) a brand image is a name, term, sign, symbol, design, or combination of these things that are used to identify products or services from one seller or group of sellers and to distinguish them from competitors. Previous research conducted by Husen et al, (2018), Apriliani (2019), Effendi et al, (2020), Dekasari & Hendri (2020), Miati (2020), andYoeliastuti et al, (2021), stated that brand image has a positive effect on purchasing decisions. Based on this description, the hypothesis can be explained as follows: H1: it is suspected that brand image has a positive effect on product purchasing decisions at Hotmie Padurenan.…”
Section: Literature Review the Effect Of Brand Image On Purchasing De...mentioning
confidence: 94%
“…Previous research conducted by Husen et al, (2018), Paputungan et al, (2018). Apriliani (2019), Dekasari & Hendri (2020), Soraya & Novi Marlena (2020), Awaliyah &Wibowo (2021), andJunaidi &Meirisa (2021), concluded that the word of mouth variable has a postive effect on purchasing decisions. Based on this description, the hypothesis can be explained as follows: H3: it is suspected that Word of mouth has a positive effect on product purchasing decisions at Hotmie Padurenan.…”
Section: The Effect Of Word Of Mouth On Purchasing Decisionsmentioning
confidence: 95%
See 1 more Smart Citation